Rancang Bangun Aplikasi Administrasi Akademik Berbasis Website Pada TK Negeri Pembina II Mojokerto - Handoko, Bagus; Sukmaaji, Anjik; Lusiani, Titik (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2021)
Academic business processes consisting of Registration, Class Distribution, TeachingÂ and Learning Activities, and Assessment.The obstacle handled by the school is the academic process which still uses a manual system which causes the decision-making process to be hampered.The solution given is to create an information system that can facilitate teacher performance in making decisions related to the preparation of teaching and learning activities.Software development starts from the specification of user requirements and continues through the stages of planning, modeling, construction (construction), and submission of the software system to users (deployment) which ends with assistance through the resulting software. This information system is designed and built according to the needs of TK Negeri Pembina II Mojokerto, namely the academic administration process for data management and also facilitates related processes related to the academic process.